DEFENSIVE LINE OF ACCUSED IN THE F RAMEWORK OF CONSTITUTIONAL LAW - Sharma, Vijaylaxmi; Yadav, Amit (International Journal of Psychosocial Rehabilitation, 2020)
The Preamble of the Indian Constitution is a master piece of prose in which every word conveys the philosophy of the free nation. The Preamble provides that the India of its dream would be "Sovereign, Socialist, Secular, Democratic, Republic". One can write volumes on each of the word used, to describe the political, economic, social status of its citizens in free India. The Preamble emphasizes on the unity and integrity of the Nation as also on the dignity of the individual.i Inspite of all these efforts protection of accused under Indian Laws are needs to be overhauled.